2018
DOI: 10.1016/j.vaccine.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Coverage and timeliness of vaccination and the validity of routine estimates: Insights from a vaccine registry in Kenya

Abstract: HighlightsA high coverage is essential if the full benefits of vaccines are to be enjoyed.A vaccine registry can help quantify the errors in coverage estimates from surveys.Vaccination coverage obtained using a survey approach overestimates coverage by 2%.Survey and administrative methods underestimate fully immunised children by ≥10%.Non-hospital delivery and stock-outs were associated with failure to vaccinate.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 34 publications
5
34
0
Order By: Relevance
“…In this study, one third of children had not completed their vaccination and the coverage rate for specific vaccines declined for subsequent doses of vaccines with high dropout rates. This finding corroborates with other evidences where missing measles and third doses of polio and pentavalent vaccine were the main reason for not being fully vaccinated [3,24,43]. In addition, the study indicated different coverage's for specific vaccines provided in the same vaccination visits.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this study, one third of children had not completed their vaccination and the coverage rate for specific vaccines declined for subsequent doses of vaccines with high dropout rates. This finding corroborates with other evidences where missing measles and third doses of polio and pentavalent vaccine were the main reason for not being fully vaccinated [3,24,43]. In addition, the study indicated different coverage's for specific vaccines provided in the same vaccination visits.…”
Section: Discussionsupporting
confidence: 91%
“…Full vaccination was defined as the child vaccination status once an infant has received all recommended vaccines included in the national schedule: a dose of Bacille Calmette Guérin (BCG); three doses of Oral Polio Vaccine (OPV); three doses each of Penta-valent and Pneumococcal Conjugate Vaccine (PCV); one dose of Inactivated Polio Vaccine (IPV); two doses of rotavirus and one dose of measles vaccines by the age of 12 months [5,22,26,40,41]. On-time vaccination for specific vaccines was defined as vaccine dose administered within 4 days prior [31,[42][43][44][45] and within 4 weeks after the recommended age specified in the national immunization schedule [12,30,31,37,[43][44][45][46][47][48][49]. On-time full vaccination was also defined as all vaccine doses administered within 4 days prior [31,[42][43][44][45] and within 4 weeks after the recommended age specified in the national immunization schedule.…”
Section: Independent Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Challenges to implementing a high-quality household survey are well-known (4,17,18) but even when surveys are well-implemented, presentation of results may be hampered by a lack of standardized definitions of potential indicators and/or failure to report enough information to define those indicators clearly (10,(19)(20)(21). WHO and partners therefore recently developed a white paper to help harmonize the collection and analysis of vaccination coverage data across the major survey programs (22).…”
Section: Introductionmentioning
confidence: 99%